Linking aberrant chromatin features in chronic lymphocytic leukemia to transcription factor networks - Jan‐Philipp Mallm; Murat Iskar; Naveed Ishaque; Lara C Klett; Sabrina J Kugler; Jose M Muino; Vladimir B Teif; Alexandra M Poos; Sebastian Großmann; Fabian Erdel; Daniele Tavernari; Sandra D Koser; et al. (Molecular Systems Biology)
Abstract In chronic lymphocytic leukemia (CLL), a diverse set of genetic mutations is embedded in a deregulated epigenetic landscape that drives cancerogenesis. To elucidate the role of aberrant chromatin features, we mapped DNA methylation, seven histone modifications, nucleosome positions, chromatin accessibility, binding of EBF1 and CTCF, as well as the transcriptome of B cells from CLL patients and healthy donors. A globally increased histone deacetylase activity was detected and half of the genome comprised transcriptionally downregulated partially DNA methylated domains demarcated by CTCF. CLL samples displayed a H3K4me3 redistribution and nucleosome gain at promoters as well as changes of enhancer activity and enhancer linkage to target genes. A DNA binding motif analysis identified transcription factors that gained or lost binding in CLL at sites with aberrant chromatin features. These findings were integrated into a gene regulatory enhancer containing network enriched for B‐cell receptor signaling pathway components. Our study predicts novel molecular links to targets of CLL therapies and provides a valuable resource for further studies on the epigenetic contribution to the disease.